Interdisciplinary and minimally invasive approach to restoring aesthetics and periodontal health using a digital workflow - Oliveira, Beatriz Almeida; Stapani, Nathalia Censi; Reis, Isabella Neme Ribeiro Dos [UNESP]; Sanchez, Renato Lardin Sartori (BMJ, 2025)
Dental veneers are a popular option for enhancing smile aesthetics. While both ceramic and composite veneers are effective, achieving optimal outcomes often requires meticulous planning and interdisciplinary collaboration. A woman in her early 30s presented with dissatisfaction due to poorly executed direct composite veneers from teeth #15 to #25, which led to biofilm accumulation and gingival inflammation. After removing the veneers, a diagnostic wax-up revealed that achieving the desired aesthetic outcome would require significant tooth preparation for some teeth and bulky veneers for others, if their current positions were maintained. Orthodontic treatment with aligners was performed to reposition the teeth, enabling a more conservative approach and natural veneers. Ceramic veneers were planned for teeth #13 to #23, digitally fabricated and cemented using adhesive protocols. At the 1-year follow-up, aesthetic, functional and periodontal stability were successfully maintained. This case highlights the benefits of interdisciplinary planning and the use of digital technologies to achieve minimally invasive treatment with ceramic veneers, respecting periodontal health and ensuring an aesthetic and natural outcome.
Keywords: Dentistry and oral medicine; Mouth